Analisis Financial Performance dan Corporate Social Responsibility Terhadap Nilai Perusahaan (Study pada Perusahaan LQ45 yang Terdaftar di BEI 2017-2019) - Hesti Setiorini; Furqonti Ranidiah; Dinal Eka Pertiwi; Adi Bambang Permadi (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2022)
The purpose of this study was to determine the effect of liquidity, leverage, profitability and corporate social responsibility on firm value. This study used secondary data. The object of the study was LQ45 companies listed on the Indonesia Stock Exchange in 2017-2019. The number of respondents were 28 companies. The data analysis technique of this study used the SPSS program and multiple linear regression. The results of the study state that liquidity has a positive and significant effect on firm value, with a sig value of 0.008. Laverage has no effect on firm value, with a sig value of 0.216. Profitability has no effect on firm value, with a sig value of 0.370 and Corporate Social Responsibility has a positive and significant effect on firm value, with a sig value of 0.039.